The disulfide relay system of mitochondria is connected to the respiratory chain - Bihlmaier, Karl (The Rockefeller University Press, 2007)
All proteins of the intermembrane space of mitochondria are encoded by nuclear genes and synthesized in the cytosol. Many of these proteins lack presequences but are imported into mitochondria in an oxidation-driven process that relies on the activity of Mia40 and Erv1. Both factors form a disulfide relay system in which Mia40 functions as a receptor that transiently interacts with incoming polypeptides via disulfide bonds. Erv1 is a sulfhydryl oxidase that oxidizes and activates Mia40, but it has remained unclear how Erv1 itself is oxidized. Here, we show that Erv1 passes its electrons on to molecular oxygen via interaction with cytochrome c and cytochrome c oxidase. This connection to the respiratory chain increases the efficient oxidation of the relay system in mitochondria and prevents the formation of toxic hydrogen peroxide. Thus, analogous to the system in the bacterial periplasm, the disulfide relay in the intermembrane space is connected to the electron transport chain of the inner membrane.